Становлення та розвиток інституту конституційного контролю в Україні - Шевчук, Ірина Миколаївна; Shevchuk, Iryna M. (Ужгородський національний університет, 2015)
У статті на основі аналізу правових актів та конституційно-правових доктрин, представлених у працях українських учених і державознавців, досліджено виникнення, становлення й розвиток інституту конституційного контролю в Україні. Охарактеризовано особливості його становлення в різні історичні періоди та визначено основні етапи формування. Зазначено, що утворення й діяльність Конституційного Суду стали можливими завдяки набуттю Україною незалежності та відходу її державно-правової думки від орієнтування на радянську практику.

The article investigates the origin, formation and development of the institute of constitutional control in Ukraine, basing on the analysis of regulations and legal constitutional doctrines, presented in the works of Ukrainian scientists and state experts. The features and the main stages of its formation in different historical periods are characterized. It was indicated that the formation and activity of the Constitutional Court of Ukraine were made possible thanks to getting of independence by Ukraine’s and the departure of its state legal opinion from targeting the Soviet practice.
Formation and development of Constitutional control institute in Ukraine
Keywords: конституційний контроль; Конституція України; Конституція УРСР; Конституційний Суд України; американська модель конституційного контролю; європейська модель конституційного контролю; constitutional control; the Constitution of Ukraine; Constitution of the Ukrainian SSR; Constitutional Court of Ukraine; American model of constitution control; European model of constitution control